Ileal Ganglioneuromatosis with Adenocarcinoma in a Patient with Multiple Neurofibromatosis - Prakash, K. (Springer-Verlag, 2011)
Von Recklinghausen’s disease or type 1 neurofibromatosis is an autosomal dominant disease characterized by mucocutaneous neurofibromas, café-au-lait spots and involves many organs including gastrointestinal tract. Gastrointestinal involvement in neurofibromatosis is uncommon and is seen 25% patients and nearly 5% of them are only symptomatic (Shekitka and Sobin, Am J Surg Pathol 18:250–257, 1994; Tomita et al., Int J Colorectal Dis 21: 89–91, 2006).